Validation efforts and flexibilities of an eight-year-old human juvenile lumbar spine using a three-dimensional finite element model. - Jebaseelan DD; Jebaraj C; Yoganandan N; Rajasekaran S; Jebaseelan, D Davidson; Jebaraj, Chidambaram; Yoganandan, Narayan; Rajasekaran, S (Medical & Biological Engineering & Computing, 2010)
The objective of this study was to develop a finite element model of the lumbar spinal column of an eight-year-old human spine and compare flexibilities under pure moments, adult, and pediatric loading with different material models. The geometry was extracted from computed tomography scans. The model included the cortical and cancellous bones, growth plates, ligaments, and discs. Adult, adolescent, and pediatric material models were used. Flexion (8 Nm), extension (6 Nm), lateral bending (6 Nm), and axial rotation (4 Nm) moments representing adult loads were applied to the three material models. Pediatric loading (0.5 Nm) was applied under these loadings to the eight-year-old spine using adult and pediatric material models. Flexibilities depended on spinal level, loading mode, and material model. Outputs incorporating the pediatric material model responded with increased flexibilities compared to the adult and adolescent material models, with one exception. This was true for the adult and pediatric loading conditions. While the sagittal and coronal bending responses were not considerably different between the adult and pediatric loadings, axial rotation responses were greater under the adult loading. This model may be used to determine intrinsic responses, such as stresses and strains, for improved characterizations of the juvenile spine behavior.